The Personal Consideration and Its Effect on Transferring the Right in Options to the Successor - حسن نور اياد; علي حميد سلطان (Journal of Legal Sciences, 2021)
It has become certain that the achievement of the purpose of the contract as a general asset is not affected by the person or qualities of the contractors, but the matter depends on the content of the contract because the achievement of the purpose of the contract is equal and identical no matter how different the person of the contractor is, however, the purpose of the contract may be affected by a certain person or a certain quality, and thus the contract is not achieved by its content. This effect is known as the personal consideration which is a subjective issue, affecting the extent of transferring the contract effects to the successor, and then the achievement of the purpose of the contract depends on a certain person by himself, especially in using the right in the option arising thereof which in turn results in preventing the transference of this right to the successor due to its relatedness to the element of consideration with the variance of the effect of that on all rights, as the effect is also variant for transferring the right in option from one type to another.